Analisis Tindak Tutur Lokusi pada Daftar Putar “Zenius: Hobby Live Class” - Intan Virhanix Aprilia; Adistia Aulia Salma; Zainab Umi Khultum; Agustin Rima Cahyani; Asep Purwo Yudi Utomo (LPPM STKIP PGRI Bandar Lampung, 2023)
The utterances of asking, ordering, begging, ordering, giving orders are a few examples of the absence of speech. A speech act is a speech which contains an action. Each speech act has the ability to convey useful information and statements. In this article, the writer is interested in analyzing the videos in the “Zenius: Hobby Live Class” playlist. The purpose of conducting this research is to discuss and look for forms of locutionary speech acts in the “Zenius: Hobby Live Class” playlist. The method used in this research is a qualitative approach and a pragmatic approach with a descriptive research type. The data used in this study came from utterances or also known as utterances in the “Zenius: Hobby Live Class” playlist. The speech acts found in the study included two categories of locutionary acts, namely, 31 utterances of locutionary acts and 9 utterances of locutionary speech acts. With this research, it is hoped that it will be useful for other readers and writers as a source of reference and can add to knowledge in the field of pragmatics.